1995
DOI: 10.1111/j.2042-7158.1995.tb03268.x
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric Distribution of Ion-exchange Resins: a Drug Delivery System for the Topical Treatment of the Gastric Mucosa

Abstract: Previous studies by this group on freeze-dried oral dosage forms containing finely-divided ion-exchange resins revealed prolonged gastric residence and uniform distribution within the stomach. The present study was carried out to ascertain whether this was due to freeze-drying, properties of the radiolabelled ionic exchange resin, or the small dosing volume used. 99mTc-labelled cholestyramine resin was administered in two dosage forms, a freeze-dried tablet which dissolved in the oral cavity (orally dissolving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…DA-6034 EFMS tablets showed enhanced gastroprotective effects in gastric ulcerinduced beagle dogs, indicating the therapeutic potential of EFMS tablets for the treatment of gastritis (158). In another example, it was found that in normal volunteers ionexchange resins achieved excellent distribution in the gastric cavity and had a prolonged gastric residence time, 20-25% remaining for 5.5 h. (155). More recent results by the same group indicate that the mechanism by which resin particles adhere to the mucosa is unlikely to be chargebased, since they persist in the stomach regardless of whether they bear a non-adhesive polymer coating and regardless of whether the stomach contains food (156).…”
Section: Dosage Forms With Prolonged Gastric Residence Timementioning
confidence: 97%
“…DA-6034 EFMS tablets showed enhanced gastroprotective effects in gastric ulcerinduced beagle dogs, indicating the therapeutic potential of EFMS tablets for the treatment of gastritis (158). In another example, it was found that in normal volunteers ionexchange resins achieved excellent distribution in the gastric cavity and had a prolonged gastric residence time, 20-25% remaining for 5.5 h. (155). More recent results by the same group indicate that the mechanism by which resin particles adhere to the mucosa is unlikely to be chargebased, since they persist in the stomach regardless of whether they bear a non-adhesive polymer coating and regardless of whether the stomach contains food (156).…”
Section: Dosage Forms With Prolonged Gastric Residence Timementioning
confidence: 97%
“…Gastro-retentive DDSs exhibiting controlled drug release are significantly important for drugs which are: Acting locally in the stomach (e.g. antibiotics against Helicobacter Pylori, antacids and misoprostol) [15][16][17][18][19].Absorbed incompletely due to a relatively narrow window of absorption in the GIT, such as cyclosporin, ciprofloxacin, furosemide, L-DOPA, p-aminobenzoic acid and riboflavin [3,[20][21][22][23][24][25].Unstable in the intestinal or colonic environment such as captopril [26] or exhibit low solubility at high pH values such as verapamil HCl, diazepam and chlordiazepoxide [27][28][29][30]. Polymers are principle excipient in pharmaceutical dosage forms especially with modified release.…”
Section: Introductionmentioning
confidence: 99%
“…Gastroretentive 3 . For such an effect, the particles will need to be small from a mechanical consideration and of low density so that they might be able to float 3 .…”
Section: Introductionmentioning
confidence: 99%
“…For such an effect, the particles will need to be small from a mechanical consideration and of low density so that they might be able to float 3 . Several approaches like floating multiparticulates system using ion exchange resin loaded with bicarbonate 4 , floating beads of riboflavin using sodium alginate solution containing CaCO 3 or NaHCO 3 as gas generating agents 5 , piroxicam in hollow polycarbonate (PC) micro spheres 6 , hollow microspheres (microballoons) loaded with either Translit or Ibuprofen in an outer enteric acrylic polymer 7 , air compartment multiple-unit system for prolonged gastric residence 8 , microspheres by core solubilization technique 9 , wax and fat embedded floating micro spheres of ibuprofen 10 , floating microspheres by different solvent evaporation technique 11 , floating-bioadhesive microspheres containing acetohydroxamic acid by quasi-emulsion solvent diffusion method 12 were developed and studied for there gastroretentive properties.…”
Section: Introductionmentioning
confidence: 99%